Método de avaliação das emissões de CO2 no ciclo de vida do BRT - Machado, Christiano Lima (2017)
Many sectors in research centers have been developing works that aim to minimize the impacts that men and their development and expansion impose through the consumption of natural resources and the increasing emission of pollutants into the atmosphere. This research focused on the analysis of the life cycle of a BRT system, having as objective to develop a tool that could predict the transportation system impacts in the planning stage. We conducted a life cycle inventory - ICV of Transcarioca corridor, newly deployed in the city of Rio de Janeiro, aiming to meet the emissions produced. Also proposed a method for calculating the emissions avoided, allowing knowing the elements that constitute the benefits and environmental damage associated with the corridor. Among the results, register the volume of less 490,348 tCO2 released to the atmosphere, the operation of vehicles with the largest portion of issue throughout the life cycle, with 72.97% and that the recovery point happens in the 16th year. The objective of the research achieved with elaboration of a tool to aid decisionmaking, which presents a methodology for calculating unprecedented, once that processes the data resulting from a life cycle analysis of facing transport allowing, therefore, the comparison between modes and the best choice of a new transport system taking into account the environmental aspects.